Peran Perguruan Tinggi Dalam Meningkatkan Sistem Pertahanan Negara Melalui Pendidikan Bela Negara - Holimin Holimin; Dartono Dartono; Djoko Prihantoro (Akademi Angkatan Udara, 2021)
The process of globalization and advances in information technology have caused major changes in the lives of the world's people. Access to information is getting easier and faster to spread throughout the country, creating global transparency where the physical boundaries of a country's sovereignty do not seem to exist, thus presenting a world without borders. Advances in technology have encouraged the formation of an increasingly transparent and open world society. This openness provides opportunities for interdependence between nations, and often leads to competition. The high level of competence can lead to an increase in the interests of a country against other countries. Indonesia as an independent and sovereign country with abundant natural resources and human resources, needs to develop awareness of state defense in the form of increasing national defense capabilities through the participation of universities, both in developing defense equipment through research and developing human resources as a defense force. The mandate of the Constitution in article 27 paragraph (3) states that every citizen has the right and is obliged to participate in efforts to defend the state. Every citizen has the right and is obliged to participate in national defense and security efforts (Article 30 paragraph 1) and Article 2 states that state defense and security is carried out through a universal people's defense and security system in which the Indonesian National Armed Forces and the Indonesian National Police are the main forces, and the people as a supporting force. Observing the constitutional order requires the role of universities in developing their contribution to the development and development of the national defense system. There is a need for a mechanism of cooperation between the Ministry of Defense and the Ministry of Education and Culture in general as well as cooperation between TNI units related to Higher Education as providers of higher education.